Liquefaction Analysis Based on Liquefaction Potential Index Method in Prambanan Temple Complex of Jogjakarta - Lisa Fitriyana; Bayu Prasetyo Afandi (Universitas Islam Sultan Agung, 2020)
Prambanan Temple is a cultural heritage located in Jogjakarta. Tectonically, the Special Region of Jogjakarta and its surroundings are an area with a fairly high level of seismic activity in Indonesia. Geotechnically, the soil in Jogjakarta is sandy with similar gradation. The thickness of the sand ranges from -50 m to -60 m. Whereas, the ground water level is located at a depth of -12 m during dry season and in rainy season, it rises from -6 m to -4 m. The impact of soil types and the high Ground Water Level (GWL) allow it for liquidation to occur during an earthquake. This study was conducted using liquefaction analysis, through Liquefaction Potential Index (LPI) method with ground water level variations. Before analyzing the liquefaction using LPI method, Peak Ground Acceleration (PGA) methods were used, and analysis could then be done through Cyclic Resistance Ratio (CRR) and Cyclic Stress Ratio (CSR) to obtain safety factors and the Liquefaction Potential Index analysis was then conducted. To analyze this liquefaction, earthquake data from 2004 to 2019 and the results of the SPT field test at the Prambanan Temple were needed. From the liquefaction potential analysis through Liquefaction Potential Index (LPI), the results showed that in CSR Seed & Idriss (1971) and CRR Tokimatsu & Yoshimi (1983), GWL 1 m at depths from 4.5 m and above, the potential of liquefaction occurrence was high. The largest PGA value was obtained based on the Matsuchka (1980) method on May 26, 2006 which was 0.102.